ANALISIS KELAYAKAN EKONOMI PADA INDUSTRI VIRGIN COCONUT OIL (VCO) DI SUKOREJO KECAMATAN SUMBERSARI KABUPATEN JEMBER - Andrew Setiawan Rusdianto; Winda Amilia; Doni Adi Nugroho (Faculty of Agricultural Technology, University of Jember, 2020)
Agroindustry is an industry that processes agricultural products from raw materials. Agroindustry increase the added value of agricultural commodities. Virgin coconut oil (VCO) product have high economic value because it has many benefits for health and beauty care as well. One of the industries processing coconut into a VCO product in Jember on an SME (Small Medium Enterprises) scale is located in Sukorejo, Jember Regency. The economic feasibility showed that its VCO industry business had a positive NPV. The BC Ratio value less than 1, which means that cash in flow was bigger than cash out flow, in the present value called Break Even Point (BEP), that is, total cost equals total revenue. IRR value that is generated is greater > 6% loan interest, and the last payback period (PBP), which is produced shows the value (less than) <10 years. In accordance with the specified time period of 5 years and 4 months. From the results of the analysis, it can be said that the VCO industry in Sukorejo, Sumbersari District was feasible to do. Keywords: economic feasibility, virgin coconut oil